Cosmological questions before Einstein - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2005)
Einstein's first cosmological work, published in 1917, marked the beginning of relativistic cosmology, but it was well founded on earlier questions concerning the world as a whole. The paper presents three such topics: the Olbers paradox, the Seeliger paradox, and speculations concerning cosmological consequences of thermodynamics together with some of their repercussions in relativistic cosmology.